EFFECT OF USING FERMENTED PALM KARNEL CAKE EXTRACT IN BROILER COMPLETE FEED COMBINED WITH MORINDA CITRIFOLIA DRINKING WATER ON FEED INTAKE, BODY WEIGHT GAIN, FEED CONVERTION AND FEED EFFICIENCY (Universitas Kanjuruhan Malang, 2014)
The aim of this research was to know the effect of using effect of using fermented palm kernel cake extract in broiler complete feed combined with morinda citrifolia drinking water on feed intake, body weight gain, feed conversion and feed efficiency. Material used in this study include cattle, cages, equipment and feed. Animals used in this study were 96 unsex strains of broiler MB-202P produced by PT. Japfa Comfeed Indonesia Tbk.The feed is a complete feed products by PT. Japfa Comfeed, Tbk. Method used was experiment. The trarment arranged with complitly random design eight treatment 4x2 factorial. Each experimental unit consist of four broiler. Which coupled with the treatment in the form of fermented products as much as 0%, 10%, 20%, and 30%. Result of this search shown that there was no significant on feed intake (P>0.05), no significant on fermented (P>0.05), no significant on interaction morinda citrifolia fermented (P>0.05). no significant on body weight gain on interaction morinda citrifolia fermented (P>0.05), no significant on feed conversion on factor morinda citrifolia fermented (P>0.05), no significant on feed efficiency on factor morinda citrifolia, no significant on feed efficiency on interaction morinda citrifolia (P>0.05). Significant on body weight gain on factor morinda citrifolai (P<0.05), very significant on factor fermented (P<0.01), very significant on feed convertion on factor femented (P<0.01), very significant on feed efficiency on factor fermented (P<0.01). It is suggested to incerese level fermented palm cernel cake and morrinda citrifolia extract in broiler.Keywords : Broiler, palm carnel cake, cassava waste, morinda citifolia, feed intake, body weight gain, feed convertion, feed efficiencyÂ